Inside Cover Image, Volume 6, Issue 5. (10th August 2016) - Bhattacherjee, Arnab; Krepel, Dana; Levy, Yaakov
Abstract : The inside cover image, by Yaakov Levy et al., is based on the Advanced Review Coarse‐grained models for studying protein diffusion along DNA, DOI:10.1002/wcms.1262 . Abstract : The inside cover image, by Yaakov Levy et al., is based on the Advanced Review Coarse‐grained models for studying protein diffusion along DNA, DOI:10.1002/wcms.1262 .